Albania Country Economic Memorandum : Background Note on Supporting an Adaptive and Resilient Labor Force - World Bank (World Bank, Washington, DC, 2022)
This background note is one of several analytical contributions to the 2021 Albania country economic memorandum (CEM). The CEM is a World Bank flagship report that aims to help Albania identify next steps in its structural reform agenda. As set out in the CEM, Albania needs to refocus attention on the pre-crisis reform agenda and accelerate its long-term economic growth rate, including by spurring productivity growth, building human capital, and supporting investment. On the labor supply side, this means investing in people and supporting workers in their transitions towards better employment. On the labor demand side, this means supporting firm productivity growth and the creation of better job opportunities. Beyond higher economic growth rates per se, however, the quality of the development model needs to strengthen. Through more green, resilient and inclusive development (GRID), Albania can ensure that growth gains will be more sustainable. Finally, the CEM highlights the need for Albania to rebuild its public finances. The Coronavirus disease 2019 (COVID-19) crisis has driven public debt to new heights. Upgrading Albania’s growth model - including implementing many of the reforms presented in the CEM - will require further spending. In this context, increasing the fiscal space available to Albania needs to be a priority.